2017
DOI: 10.1186/s12889-017-4241-8
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve engagement of ‘hard to reach’ older people in research on health promotion: a systematic review

Abstract: Background: This systematic review aimed to identify facilitators, barriers and strategies for engaging 'hard to reach' older people in research on health promotion; the oldest old (≥80 years), older people from black and minority ethnic groups (BME) and older people living in deprived areas. Methods: Eight databases were searched to identify eligible studies using quantitative, qualitative, and mixed research methods. Using elements of narrative synthesis, engagement strategies, and reported facilitators and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 42 publications
(129 reference statements)
4
94
0
2
Order By: Relevance
“…Our findings, in accordance with other studies, demonstrate that the social relation aspect is an important motive for engagement in community-based health promotion interventions [21,37,38]. In investigating the motivation for residents of deprived areas of social housing to engage in health promotion interventions, a systematic review of strategies to improve engagement of hard-to-reach older adults emphasized that participants preferred group-based health promotion interventions compared to individual sessions because of their social element [21]. The establishment of new relations to fellow residents and the enhancement of existing relations among residents in our study are health promoting, since positive social relations are favorable for both the physical and mental health and overall wellbeing of individuals [7,8].…”
Section: Social Relations and Community Engagement As Motives And Persupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings, in accordance with other studies, demonstrate that the social relation aspect is an important motive for engagement in community-based health promotion interventions [21,37,38]. In investigating the motivation for residents of deprived areas of social housing to engage in health promotion interventions, a systematic review of strategies to improve engagement of hard-to-reach older adults emphasized that participants preferred group-based health promotion interventions compared to individual sessions because of their social element [21]. The establishment of new relations to fellow residents and the enhancement of existing relations among residents in our study are health promoting, since positive social relations are favorable for both the physical and mental health and overall wellbeing of individuals [7,8].…”
Section: Social Relations and Community Engagement As Motives And Persupporting
confidence: 93%
“…Engagement in the intervention was driven by a desire to establish and enhance social relations. Our findings, in accordance with other studies, demonstrate that the social relation aspect is an important motive for engagement in community-based health promotion interventions [21,37,38]. In investigating the motivation for residents of deprived areas of social housing to engage in health promotion interventions, a systematic review of strategies to improve engagement of hard-to-reach older adults emphasized that participants preferred group-based health promotion interventions compared to individual sessions because of their social element [21].…”
Section: Social Relations and Community Engagement As Motives And Persupporting
confidence: 90%
See 1 more Smart Citation
“…Barriers to engagement for more fragile and harder to reach individuals were also addressed by reaching out to the most populous multi-unit retirement residences. 51 Patient Experience Journal, Volume 5, Issue 3 -2018 Study participants included persons who were living independently. Persons who are residing in assisted living facilities have more functional decline and require more support and resources.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…From within groups of older people from BAME communities, the authors found that both convening social group sessions and strengthening community connections facilitated health promotion activities. However, together with language and cultural differences, barriers included members not having the confidence or motivation to get involved …”
Section: Introductionmentioning
confidence: 99%